DEVELOPMENT OF STEM-BASED SCIENCE LEARNING MODULE ON LOCAL WISDOM OF MANGO CULTIVATION IN PROBOLINGGO ON MODERN BIOTECHNOLOGY TOPIC - Istianah Istianah; Mochammad Iqbal (ScienceEdu, 2022)
This study aims to produce an integrated STEM science learning module with local wisdom "Mango cultivation" located in Probolinggo and to find out the students' responses to the subject on the topic of modern biotechnology. This module provided reference for providing science material as well as insight into local wisdom knowledge to empower students and create awareness of maintaining, preserving and developing their environment. The learning process based on local wisdom not just convey culture to students, but rather uses the culture so that students find meaning, creativity, and gain deeper understanding of the material. The modules developed discussed of subject matter, and also link learning materials with local wisdom in terms of STEM. In integrating STEM, students not only directed to understand the material but also given guidance to provide solutions in solving a problem that occurs in local wisdom of mango cultivation in Probolinggo related to modern biotechnology materials in junior high school. This type of research is development research with 4-D research design. This research was conducted at SMP Negeri 2 Probolinggo. The results of this study are the validation of the instructional study that gets score of 3,60 score and the validation of the technical review that gets a score of 3,89 so that the validation results of the product developed are valid. Based on the analysis of student responses showed a very positive attitude towards the developed module. It can be concluded that this development module is valid and can be used as teaching material.